Analisis dan Perancangan Aplikasi Manajemen Organisasi Karang Taruna dalam Membantu Mengelola Sumber Daya Karang Taruna - Bambang Pramudhita Budhiman; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
To help address the problem of lack of participation of youth in Karang Taruna due to the lack of a system that is able to accommodate all organizational activities carried out by Karang Taruna, the author felt it was necessary to create an organizational management application that could help the performance and internal management in the Karang Taruna named Makna. The design of this Makna application is done using the Prototype Model method because in this method, it can be done the design of an interactive application prototype. as well as in the collection of data is also conducted interview methods and analysis of Business Processes. This research resulted in Unified Modelling Language (UML) design, diagrams and application interface design. After that, in order to ensure the feasibility of the application prototype to be accepted by prospective users, an application interface test with a Usability Testing approach is conducted. Usability Testing test on the design of this Makna application gets enough results to be accepted by prospective users later.